Optimizing MSME Profits through Determining the Cost of Production with the Full Costing Method at CV Rijiki Tolitoli Regency: Optimalisasi Keuntungan UMKM melalui Penentuan Biaya Produksi dengan Metode Full Costing di CV Rijiki, Kabupaten Tolitoli - Riska Riska; Edi Yanto; A. Irfan Efendi; Maskur Maskur (International Journal of Economic Entrepreneurship and Business Management, 2025)
This study aims to determine the determination of the cost of production in determining the selling price using the full costing method on CV.Rijiki Advertising as one of the MSMEs in Tolitoli Regency, This type of research is quantitative descriptive. The location of the research was carried out on CV. Rijiki Advertising which is located on Jl.Rajawali, Tuweley Village, Tolitoli Regency. Data collection was carried out using observation, interview and documentation methods with the analysis method used was the full costing method to determine the cost of production and selling price. The results of the research using the full costing method can produce a more accurate cost of production and selling price because it takes into account all production costs, then it can be known that the calculation of the cost of production of billboards in 2021 is Rp.174,342 with a selling price of Rp.290,000 by following the percentage of profit that follows the market price of 64.5%, in 2022 of Rp174,844 with a selling price of Rp.284,000 by following the percentage of profit that drops to 62.5%, in 2023 amounting to IDR 174,429 with a selling price of IDR 289,000 by following the percentage of profit according to the market price increased to 65.5%.